A preliminary account of phonological and morphophonological perception in young children with and without otitis media - Petinou, Kakia; Schwartz, R.; Gravel, J.; Lawrence, J.R. (My University, 2001)
This investigation examined the effects of otitis media with effusion (OME) and its associated fluctuating conductive hearing loss on the perception of phonological and morphophonological /s/ and /z/ in young children. We predicted that children free of OME (OME) would perform better than children with histories of OME (OME+). We also predicted that for the OME+ group morphological perception would be harder than phonological perception, because the former category carries an additional linguistic load (i.e., plurality). Sixteen children, ages 26 to 28 months (M =26.5, SD=0.6) were divided into two groups, the OME (n =8) and OME + (n =8) based on OME history during the first year of life. Subjects in the OME group were free of the disease for 4/5 visits and pure tone average (PTA) was 12.6 dB HL (SD=4.8). Subjects in the OME+ group had the disease on 3/5 visits and PTA was 23dB HL (SD=2.7). Experimental stimuli were six monosyllabic novel word-pairs. Members of each word-pair differed only in the presence of final voiced or voiceless fricative, marking the targets phonologically (e.g., [g6]/[g6 s] as in ‘law’, ‘loss’) or morphophonologically (e.g., [dæp]/[dæps] as in ‘map’ ‘maps’). Subjects were taught the unfamiliar word pairs using a fast mapping procedure. Perception was tested with the bimodal preferential looking paradigm. Children in the OME group performed significantly better than their OME+ counterparts. Individual word-pair analyses showed that OME+ group performed more poorly than the OME group on one phonological and on two morphological targets, all ending with [s]. For the OME+ group, targets with final [s] posed greater difficulty than those with final [z], especially on morphophonological plural-{s) targets. The results suggested that the fluctuating hearing loss associated with OME might have a negative impact on speech perception.
Keywords: Morphophonological perception; Otitis media; Phonological perception